Angiotensin II-Related Activation of Scleral Fibroblasts and Their Role on Retinal Ganglion Cell Death in Glaucoma - Si-Eun Oh; Jie-Hyun Kim; Hee-Jong Shin; Seong-Ah Kim; Chan-Kee Park; Hae-Young Lopilly Park (MDPI AG, 2023)
We identify the angiotensin II (AngII)-associated changes in the extracellular matrix (ECM) and the biomechanical properties of the sclera after systemic hypotension. Systemic hypotension was induced by administering oral hydrochlorothiazide. AngII receptor levels and ECM components in the sclera and biomechanical properties were evaluated based on the stress-strain relationship after systemic hypotension. The effect of inhibiting the AngII receptor with losartan was determined in the systemic hypotensive animal model and the cultured scleral fibroblasts from this model. The effect of losartan on retinal ganglion cell (RGC) death was evaluated in the retina. Both AngII receptor type I (AT-1R) and type II (AT-2R) increased in the sclera after systemic hypotension. Proteins related to the activation of fibroblasts (transforming growth factor [TGF]-β1 and TGF-β2) indicated that transformation to myofibroblasts (α smooth muscle actin [SMA]), and the major ECM protein (collagen type I) increased in the sclera after systemic hypotension. These changes were associated with stiffening of the sclera in the biomechanical analysis. Administering losartan in the sub-Tenon tissue significantly decreased the expression of AT-1R, αSMA, TGF-β, and collagen type I in the cultured scleral fibroblasts and the sclera of systemic hypotensive rats. The sclera became less stiff after the losartan treatment. A significant increase in the number of RGCs and decrease in glial cell activation was found in the retina after the losartan treatment. These findings suggest that AngII plays a role in scleral fibrosis after systemic hypotension and that inhibiting AngII could modulate the tissue properties of the sclera, resulting in the protection of RGCs.